2021
DOI: 10.1021/acssuschemeng.1c01848
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Property-Tailored Soy Protein Extraction Process Using a Deep Eutectic Solvent

Abstract: Using soy protein as a model and deep eutectic solvent as the extraction solvent, the effects of key factors on the extraction of soy protein based on monitoring its molecular properties were systematically studied. The conditions for the recovery of soy protein from deep eutectic solvents were explored and optimized using the response surface methodology. In addition, the influence of the deep eutectic solvent on the structure and physicochemical properties of soy protein was studied using various characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…They compared the extraction efficiency obtained with this mixture to a method using an aqueous solution of sodium hydroxide. The experiment resulted in an extraction yield enhanced by 60%, which ultimately provides another proof of DESs’ suitability for the extraction of proteins from renewable raw biomasses ( Chen et al, 2021 ).…”
Section: Deep Eutectic Solvents As Media For Protein Extractionmentioning
confidence: 84%
See 1 more Smart Citation
“…They compared the extraction efficiency obtained with this mixture to a method using an aqueous solution of sodium hydroxide. The experiment resulted in an extraction yield enhanced by 60%, which ultimately provides another proof of DESs’ suitability for the extraction of proteins from renewable raw biomasses ( Chen et al, 2021 ).…”
Section: Deep Eutectic Solvents As Media For Protein Extractionmentioning
confidence: 84%
“…Convergently, Chen et al (2021) mixed ChCl with glycerol for the extraction of soy protein and observed that DES-based extraction showed a yield higher by 10% than that of the acid-based precipitation method. Soy protein extracted by means of DESs also showed improved heat resistance and better hydrophobicity than native soy protein, indicating that DESs can enhance the physical properties of the proteins they solubilize, and thus, they can be further used as functional ingredients.…”
Section: Deep Eutectic Solvents As Media For Protein Extractionmentioning
confidence: 99%
“…Chen, Chaihu, Yao, Cao, Bi, Lin, and Chen [ 91 ] used CHCL:glycerol DES as the extraction solvent to extract soy proteins and noticed that DES-extraction resulted in approximately 10% higher yield ( w/w ) as compared to the conventional alkali solution acid precipitation method. In addition, the soy proteins extracted by DES exhibit better heat resistance and stronger hydrophobicity than commercial soy proteins, indicating that DES can improve the functional properties of proteins and the extracted proteins may be used as new functional material.…”
Section: Des Extraction Of Biological Macromoleculesmentioning
confidence: 99%
“…Some DESs are easily recovered by adding water, or PEER-REVIEWED REVIEW ARTICLE bioresources.com with vacuum distillation (Luo et al 2022;Tian et al 2017;Shen et al 2019). There are multifarious substances that can be dissolved in DESs, such as metals (Abbott et al 2004), bioactive substances (Wagle et al 2014;Gállego et al 2015), and protein (Chen et al 2021). It is interesting to find that when it is used to extract proteins, DESs have much higher extraction efficiency and recovery rate than water and conventional organic solvents (Nakhle et al 2021).…”
Section: Extraction and Microextractionmentioning
confidence: 99%